Formal Defection from Eastern Non-Catholic Church and Marriage Validity: Canon 781 - Strickland, Amy J. (CLSA advisory opinions, 2001-2005, 2001)
A baptized Protestant man who wishes to marry a Catholic woman has approached our tribunal for a declaration of invalidity. He was married to a Russian woman in a Russian civil ceremony in 1997. As an infant, this woman was sacramentally initiated into the Russian Orthodox Church. But, as an adult, she was "re-baptized" into a Protestant tradition. At the time of the marriage in question, the woman considered herself a member of this Protestant body. Can she be considered to have formally defected from the Russian Orthodox Church, or should the union be considered invalid due to a defect of sacred rite?